2015
DOI: 10.1155/2015/391234
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Gelatin Seed Treatment as a Biostimulant of Cucumber Plant Growth

Abstract: The beneficial effects of gelatin capsule seed treatment on enhanced plant growth and tolerance to abiotic stress have been reported in a number of crops, but the molecular mechanisms underlying such effects are poorly understood. Using mRNA sequencing based approach, transcriptomes of one- and two-week-old cucumber plants from gelatin capsule treated and nontreated seeds were characterized. The gelatin treated plants had greater total leaf area, fresh weight, frozen weight, and nitrogen content. Pairwise comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…In the same study, increased gene expression of the three tricarboxylic acid cycle enzymes, nitrate reductase, and asparagine synthetase was confirmed by reverse transcriptasepolymerase chain reaction in the roots following application of alfalfa hydrolysate. Wilson et al (2015) suggested that gelatin, an animal protein, increased expression of amino acid and N transporter genes, which may be responsible for enhanced N uptake by roots.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, increased gene expression of the three tricarboxylic acid cycle enzymes, nitrate reductase, and asparagine synthetase was confirmed by reverse transcriptasepolymerase chain reaction in the roots following application of alfalfa hydrolysate. Wilson et al (2015) suggested that gelatin, an animal protein, increased expression of amino acid and N transporter genes, which may be responsible for enhanced N uptake by roots.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin, an animal-derived protein, applied as capsules placed near the seeds, has been shown to act as a biostimulant on greenhouse-grown cucumber ( Cucumis sativus L.). Application of these gelatin capsules increased fresh and dry weight biomass, leaf area and nitrogen content of 2-week old plants compared with seeds sown without gelatin capsules ( Wilson et al, 2015 ). Changes in plant biomass and nitrogen in response to the gelatin capsules were correlated with an up-regulation of both amino acids and N transporter genes and the xenobiotic detoxification system.…”
Section: Effects On Physiological and Agronomic Traits Of Cropsmentioning
confidence: 99%
“…The EC and USDA have now provided a framework for the regulation and use of biostimulants in Europe and the US respectively. In line with the (EU) 2019/1009 regulation and the onus that it placed on manufacturers to justify a biostimulant claim, EBIC has proposed some general guiding principles to follow when justifying plant biostimulant claims [119].…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that APR ® might preventively prepare plants to oxidative stresses by the regulation of ROS signaling genes, in this study SOD1A gene was clearly regulated in the presence of stress and APR. In another study by Wilson et al (2015), gelatin capsules were applied in soil near cucumber seeds and caused the increase in fresh and dry weight biomass, leaf area and nitrogen content of 2-week old plants. These improvements were credited to an upregulation of both amino acids and N transporter genes and the xenobiotic detoxification system [119].…”
Section: Plant Biostimulants' Mode Of Actionmentioning
confidence: 99%